Animal models for bisphosphonate‐related osteonecrosis of the jaws ‐ an appraisal. (25th January 2013) - Sharma, D; Hamlet, S; Petcu, E; Ivanovski, S
<x xml:space="preserve">Abstract</x> The prolonged use of bisphosphonates has been shown to cause a condition termed 'bisphosphonate related osteonecrosis of the jaws' (BRONJ). BRONJ is a disease entity which has only been described relatively recently, and its multi‐factorial aetiology is yet to be fully elucidated. Therefore, the treatment of BRONJ lesions remains a challenge, and animal models are necessary to assist researchers in better understanding the disease. This has led to the recent publication of a number of studies utilising a variety of animal models of BRONJ. This review outlines the factors to be considered when selecting an animal model for BRONJ and discusses the current literature in this rapidly progressing field of research. It is important to consider the applicability of a given model to the clinical condition presenting in humans, and to this end, thorough characterisation of the clinical, histological, radiographic and systemic features is necessary. The development of a clinical lesion is an important consideration in terms of choosing a relevant model, and it appears clear that surgical manipulation, generally involving tooth extraction, is necessary for successful induction of the classic 'clinical' lesion of BRONJ.